OBTAINING FOOD SAFETY BY APPLYING HACCP SYSTEM - ION CRIVEANU; NATALIŢA MARIA SPERDEA; RADU CATALIN CRIVEANU (Annals of the University of Petrosani: Economics)
In order to increase the confidence of the trading partners and consumers in the products which are sold on the market, enterprises producing food are required to implement the food safety system HACCP,a particularly useful system because the manufacturer is not able to fully control finished products . SR EN ISO 22000:2005 establishes requirements for a food safety management system where an organization in the food chain needs to proove its ability to control food safety hazards in order to ensure that food is safe at the time of human consumption. This paper presents the main steps which ensure food safety using the HACCP system, and SR EN ISO 20000:2005 requirements for food safety.